Effects of Microdose Fertilizers and Irrigation Depth on Onion () Growth Under Drip Irrigation in Northern Ethiopia - Aemro Wale; Messay Abera; Tesfa Asmelie; Gashaw Beza (Air, Soil and Water Research)
The variables that most significantly affect bulb yield in Ethiopia’s irrigated agricultural onion production systems are the amount of irrigation water and the irrigated fertilizer application rates. North Ethiopia has gradually adopted drip irrigation for onion farming due to significant water savings and improved water and fertilizer use efficiencies. However, the optimal irrigation water (I) and fertilizer application rates (F) for drip irrigation are still unknown; field experiments using a random complete block design in factorial arrangement were conducted during summer season of 2019/2020 and 2020/2021 to explore the effects of irrigation water and fertilizer application rates on onion production and productivity. The trials were carried out at four recommended microdose fertilizer rates for nitrogen (N) and phosphorus (P 2 O 5 ; F 1 -125%, F 2 -100%, F 3 -75%, and F 4 -50%) and three different irrigation water levels (I 1 -100%, I 2 -75%, and I 3 -50%). The interaction effect of water amount and microdose fertilizer application rate significantly ( p  ⩽ .05) affected onion yield, yield-related components, and water productivity. A combined analysis of variance using SAS software 9.0 revealed that the interaction between irrigation depth and fertilizer rate had a significant ( p  ⩽ .05) impact on yield, yield-related components, and water productivity. Onion production and water use efficiency (WUE) increased significantly with increasing irrigation water and microdose fertilizer application rates. However, irrigation water less than 100% were not beneficial to the above parameters. In the two-season study, a maximum onion yield of 39.22 t ha −1 was obtained at F 1 I 1 , with a WUE of 8.20 kg m −3 . All the factors related to growth, yield, and yield-related components, the combination of a microdosing fertilizer application of 172.5 N and 86.25 P 2 O 5 kg ha −1 and 100% water per irrigation was the best drip irrigation pattern for onion. These findings provide a scientific basis for drip irrigation and microdosing fertilizer management of onions in northern Ethiopia.